"Wait and See": Effects of Matching Visual Stimulation on Impulsive Behavior during an Adaptation of Flora et al.'s (1992) Choice Task. - Hurtado-Parrado, Camilo; Cifuentes, Julián D.; Henao, Karen; Bohórquez, Carolina; Sanchez, Christian; Forigua, Juan Carlos; Arias-Higuera, Monica; Velasquez, Julian Camilo; Acevedo-Triana, Cesar (Psychological Record, 2023)
Flora et al. (The Psychological Record, 42(4), 505–517, 1992, The Psychological Record, 53, 243–252, 2003) reported that response-independent aversive noise and cold water increased impulsive responses during a choice task in which participants earned points exchangeable for money. The impulsive option immediately produced 2 points. The self-controlled option produced 10 points after a 16-s delay. Common to those studies was the pain-related nature of the aversive stimulation implemented; however, it is unknown if other types of aversive stimulation (e.g., symbolic, nonpain-related; Crosbie, 1998) would produce the same effect. The present study tested if aversive images from the International Affective Picture System (IAPS; Bradley & Lang, 2007) increased impulsive responses during a systematic replication of Flora et al.'s (The Psychological Record, 42(4), 505–517, 1992) procedure. During interspersed trials added to the original choice task, college students (126; 60 men, 66 women) searched for a stimulus hidden in aversive, appetitive, or neutral IAPS images. This matching-to-sample task was intended to increase interaction with the images. Preference for the self-control option was observed in the absence of matching trials, which replicated Flora et al.'s (The Psychological Record, 42(4), 505–517, 1992) control condition and underscored the generality of the choice task. Matching IAPS images, irrespective of their valence, increased the number of impulsive responses, reaching indifference. This pattern of indifference resembled that observed in previous studies in which both aversive or nonaversive stimuli (noise and lukewarm water) were implemented. Procedural aspects possibly explain these results, including aversive or distracting effects of frequent failure to match the images, weak-eliciting functions of the visual stimuli, or differences in trial-by-trial and overall (all trials) rates of reinforcement. Flora et al.'s task overall shows promise to continue studying how contextual factors may affect impulsive behavior, including other aversive stimuli (e.g., point loss).